1985
DOI: 10.1111/j.1432-1033.1985.tb09337.x
|View full text |Cite
|
Sign up to set email alerts
|

The pH dependence of the electron self‐exchange rate of azurin from Pseudomonas aeruginosa as studied by 1H‐NMR

Abstract: The electron self-exchange rate of azurin from Pseudomonas aeruginosu has been measured by proton NMR as a function of temperature under various conditions of pH, buffer and ionic strength. The rate does not appear very sensitive to variations in the latter parameters. Qualitative thermodynamic compensation is observed for the entropy and enthalpy of activation, with a compensation temperature of 309 7 K, and an average exchange rate of 1.3 x 106 M -' s K ' . The observed high entropy of activation contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…The first site was identified as the surface close to His35. The second was a hydrophobic patch located around the copper ligand His117, also involved in the self-exhange reaction of azurin (Groeneveld & Canters, 1985. In later investigations the role of the His35 patch has been challenged and it has been concluded further that the His35 patch and His35, in particular, is not directly involved in the electron transfer, Van de Kamp, Floris, Hali & Canters (1990) have tentatively suggested that the hydrophobic patch around His117 in azurin is also involved in the electron-transfer reaction with cytochrome c55~.…”
Section: Introductionmentioning
confidence: 99%
“…The first site was identified as the surface close to His35. The second was a hydrophobic patch located around the copper ligand His117, also involved in the self-exhange reaction of azurin (Groeneveld & Canters, 1985. In later investigations the role of the His35 patch has been challenged and it has been concluded further that the His35 patch and His35, in particular, is not directly involved in the electron transfer, Van de Kamp, Floris, Hali & Canters (1990) have tentatively suggested that the hydrophobic patch around His117 in azurin is also involved in the electron-transfer reaction with cytochrome c55~.…”
Section: Introductionmentioning
confidence: 99%
“…The self-exchange ET rate for Pseudomonas azurin has been determined by both 'H NMR and rapid-freeze ESR, and the rate constant at 298 K is in the range 0.4-1.4 x 106 M-ls-1 (14)(15)(16)(17). The rate is fairly insensitive to pH and ionic strength and the activation entropy is relatively favorable (15).…”
Section: Resultsmentioning
confidence: 99%
“…The rate is fairly insensitive to pH and ionic strength and the activation entropy is relatively favorable (15). In azurin, the copper atoms are buried in the protein interior -7 A below the hydrophobic surface patch around the Cu ligand His-117.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations